Non-invasive photoplethysmography and contact pressure optical fibre sensor - Liu, Chong (2020)
In healthcare, measurement of the photoplethysmogram (PPG) can be used for diagnosing diseases (e.g. hypoxaemia, vascular and heart diseases) and measuring a patient’s physiological parameters (blood oxygen saturation and heart rate). For measuring PPG signals, the contact force between the skin and the sensor plays an important role since both insufficient and too high contact pressure will distort the PPG signal. It would therefore be advantageous to develop a sensor that could measure contact pressure and PPG simultaneously.